Estudo e construção de dispositivos conversores de energia solar em elétrica através de sistemas supramoleculares de rutênio-cromo e rutênio-rutênio - Santos, Wagner Batista dos (2005)
The synthesis and determination of some properties of ruthenium monomers like trans-[Ru(NH3)4(L)(bpa)](BF4)2 (where L = pyridine, 4-picoline, 4-acetylpyridine and bpa = 1,2-bis(4-pyridil)ethane); cis-[Ru(dcbH2)(dypy)Cl2]Cl where dcbH2 = 4,4 -dicarboxy 2,2 bipyridine, chromium monomer like cis-[Cr(dcbH2)2Cl2]Cl; polynuclear systems Ru(II)-Cr(III) like cis-{trans-[Ru(NH3)4(L)(bpa)]}2[Cr(dcbH2)2](BF4)4Cl3 and polynuclear sistems Ru(II)-Ru(III) like cis-{trans- [Ru(NH3)4L(bpa)]}2 [Ru(dcbH2)(dipy)](BF4)4Cl3. Those compounds presented in their ultraviolet-visible electronic spectra, bands in both regions. The bands of absorption of the monomers in the regions of the ultraviolet can be attributed to internal transitions of the ligante. π - π* (IL). In the region of the visible, the electronic spectra of the ruthenium monomers present an or two denominated bands of TCML. The most intense band and of smaller energy it is denominated of TCML-1, and the more energetics, however of smaller intensity it is TCML -2. The chromium complexes, synthesized using bidentate ligand without substituents, normally present a series of three bands in their absorption spectrum. However, the compound investigated by us only showed two bands which were attributed to a vibracional co-excitation of the coupling between the d-d transition and the internal vibration transition of the ligand. The ruthenium (III) complexes showed two bands which were attributed to a vibracional coexcitation of the coupling between the d-d transition and the internal vibration transition of the ligand and two metal-ligand charge transfer bands (MLCT) low intensity. The polynuclear system produced from the chromium, ruthenium (III) and ruthenuim (II) monomers, presented the ame spectral characteristics as the compounds used in their synthesis or-be-it bands corresponding to MLCT (characteristic of the ruthenium monomer), d-d (characteristic of the chromium and ruthenium (III) monomers) and the IL (characteristic of the internal ligand transitions). The IR spectra show the differences and similarities betweem the several ruthenium monomers. The monomers containing isonicotinamide and XII the 4-acetylpyridine present a peak in the 1600 cm-1 spectral region, characteristic of the substituted -C=O group. The compounds polynuclear spectra permit their differentiation analyzing the 3300 cm-1 spectra region due to the COOH group of the chromium monomerpossible other differences are mashed by the very large spectral bands of the carboxy groups. In a general way the picks found for the composition cis-[Ru(dipy)(dcbH2)Cl2]Cl, were found for the polynuclear sistems Ru(II)-Ru(III), more intense. The reduction formal potentials, Ef, of the ruthenium monomers and polynuclear system were determined using ciclyc voltammetry for aqueous solvents. Ef value increse with increasing with drawing capacity and decreasing donor capacity of the pyridine ligands. the monomer voltammogram support the existence of a simple ruthenium specie. The polynuclear voltammograms support na increase of Ef with increasing with drawing (capture) capacity of the pyridine ligand. The photoaquation reactions of the several synthetized complexes were investigated. The compounds were photolysed at several wavelengths and products formed analysed potentiometrically (NH3) and by ion exchange (pyridine ligands). According to the cassification proposed by Molouf and Ford the compounds can be classified as non-reactive due to the low quantum yield observed the dependence on the wavelength of the reaction. Were prepared solars cells for the polynuclear system of cis- {trans-[Ru(NH3)4L(bpa)]}2[Cr(dcbH2)2](BF4)4Cl3 and cis-{trans -[Ru(NH3)4L(bpa)]}2 [Ru(dcbH2)(dipy)](BF4)4Cl3; where L = 4-acpy, 4-pic, py and isn, through method proposed by Grätzel, to verify the potentiality of these compounds in the process of conversion of energy. The obtained results are to each other quite close, however the values of Isc and Voc are very low, indicating that the conversion process for that series of compositions is not effective.